Asimov's chronology of science and discovery - Asimov, Isaac 1920-1992 (Harper & Row, 1989)
From 4 million b.c. to the present, Asimov gives entries on major scientific breakthroughs in chronological order. Annotation. Combining world history with scientific discoveries and inventions, Asimov illustrates, in chronological order, how science and cultural, social, and political events have affected each other. A good reference for the general reader. No bibliography.
Keywords: Geschichte Anfänge-1993; Geschichte; Ciencia - Aspectos sociales; Découvertes scientifiques - Histoire; Invenciones - Historia; Sciences - Aspect social; Sciences - Histoire; Gesellschaft; Naturwissenschaft; Discoveries in science -- History; Inventions -- History; Science -- History; Science -- Social aspects; Science -- history; Entdeckung; Erfindung; Wissenschaft; Naturwissenschaften; Zeittafel